Study the capability of Ecliptaalba plant to remove of lead from the polluted water by phytoremediation technique - R. Majeed, Majid; A. Jasim, Hiba; S. Mohammed, Ali (Iraqi Journal of Science, 2023)
One of the major environmental problems is the pollution of water and soilsby toxicheavy metals.The aim of current study was estimatation the ability of Eclipta albaplant for the removal of (Pb) from the polluted water by phytoremedation techniqueand study the effect of a number of parameters(Pb concentration, contact time andpHvalues). The plant showed higher removal efficiency (99.2%) after 7 days oftreatment at 50ppm.The best removal efficiency of Pb 98.95% at 100ppm wasoccurred at pH7. The root ability to accumulate Pb was more than the shoot ability,after 7 days treatment of water and pH=7, they were 2852.5 mg/kg, 2497.5 mg/kgand 502.5 mg/kg in roots, stems and leaves respectively. These results showedthatEcliptaalba can be used in biological treatment of polluted water.